1992
DOI: 10.1523/jneurosci.12-05-02000.1992
|View full text |Cite
|
Sign up to set email alerts
|

5-hydroxytryptamine1B receptors block the GABAB synaptic potential in rat dopamine neurons

Abstract: Intracellular recordings were made from presumed dopamine-containing neurons in slices cut from the midbrain of the rat. Focal electrical stimulation produced a hyperpolarizing synaptic potential that was reduced by 75-95% by the GABAB-receptor antagonist 2-hydroxysaclofen (300 microM). 5-HT (3-100 microM) reduced the amplitude of the GABAB synaptic potential by 20-74%, with a 50% reduction at 10 microM, but did not reduce the amplitude of synaptic potentials mediated by GABAA receptors. 5-HT acted presynaptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
143
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(163 citation statements)
references
References 25 publications
(35 reference statements)
19
143
0
1
Order By: Relevance
“…Mismatches between mRNA and binding sites reveal that 5HT 1B and 5HT 1D receptors are expressed predominantly on nerve terminals (Boschert et al, 1994;Maroteaux et al, 1992). Consistent with its presynaptic location, 5HT 1B receptor activation has been shown to cause presynaptic inhibition of glutamate-mediated EPSCs in many brain regions such as the hypoglossal nucleus (Singer et al, 1996) and nucleus accumbens (Muramatsu et al, 1998), and to inhibit GABA-mediated transmission in structures such as the dorsolateral septum (Matsuoka et al, 2004) and substantia nigra (Johnson et al, 1992;Stanford and Lacey, 1996). Results of the present study clearly show that 5HT 1B receptor activation also causes presynaptic inhibition of transmission in the STN.…”
Section: Discussionmentioning
confidence: 92%
“…Mismatches between mRNA and binding sites reveal that 5HT 1B and 5HT 1D receptors are expressed predominantly on nerve terminals (Boschert et al, 1994;Maroteaux et al, 1992). Consistent with its presynaptic location, 5HT 1B receptor activation has been shown to cause presynaptic inhibition of glutamate-mediated EPSCs in many brain regions such as the hypoglossal nucleus (Singer et al, 1996) and nucleus accumbens (Muramatsu et al, 1998), and to inhibit GABA-mediated transmission in structures such as the dorsolateral septum (Matsuoka et al, 2004) and substantia nigra (Johnson et al, 1992;Stanford and Lacey, 1996). Results of the present study clearly show that 5HT 1B receptor activation also causes presynaptic inhibition of transmission in the STN.…”
Section: Discussionmentioning
confidence: 92%
“…Supporting this circuitry, administration of the 5-HT1B agonist CP 93129 inhibits high-potassium-induced [ 3 H]GABA release from VTA slices (Yan and Yan, 2001b). Additionally, work in rat and guinea pig slices of the VTA has shown that the application of 5-HT or a 5-HT1B agonist reduces the amplitude of GABA-B IPSPs in DA neurons (Johnson et al, 1992;Williams, 1994, 1995). Coadministration of a 5-HT1B antagonist blocked the inhibitory effect of 5-HT on the GABA-B IPSP (Johnson et al, 1992;Cameron and Williams, 1995), while spiperone, an antagonist for 5-HT1A/2 receptors, did not (Johnson et al, 1992).…”
Section: Mesolimbic Pathwaymentioning
confidence: 97%
“…Additionally, work in rat and guinea pig slices of the VTA has shown that the application of 5-HT or a 5-HT1B agonist reduces the amplitude of GABA-B IPSPs in DA neurons (Johnson et al, 1992;Williams, 1994, 1995). Coadministration of a 5-HT1B antagonist blocked the inhibitory effect of 5-HT on the GABA-B IPSP (Johnson et al, 1992;Cameron and Williams, 1995), while spiperone, an antagonist for 5-HT1A/2 receptors, did not (Johnson et al, 1992). Some investigators propose that the relevant 5-HT1B heteroreceptors are located on the axon terminals of GABAergic projection neurons from the NA (O'Dell and Yan and Yan 2001a).…”
Section: Mesolimbic Pathwaymentioning
confidence: 99%
“…A typical effect caused by an increased serotoninergic tone in the ventral midbrain is a depression of the GABA B postsynaptic potential on the DAergic neurons (Cameron and Williams 1994;Johnson et al 1992). Accordingly, MDMA (10 mol/L) reversibly diminished the amplitude of the GABA B inhibitory potential by 49.5% Ϯ 7 % (n ϭ 4, p Ͻ .05), and this effect was antagonized by pindolol (300 nmol/L; n ϭ 4, p Ͻ .05; Figure 5).…”
Section: The Gaba B Inhibitory Postsynaptic Potential (Ipsp) Is Reducmentioning
confidence: 99%